Place quality in high-speed rail station areas: Concept definition - Du, Jinglun; Druta, Oana; van Wesemael, Pieter (Journal of Transport and Land Use, 2021)
High-speed railway (HSR) station areas are expected to benefit urban environments, not simply as transportation or economic hubs but also as urban places contributing to living quality. However, the relationship between HSR and place quality has not received systematic attention, despite the evolution of urban planning paradigms toward a clearer focus on quality of life. We have reviewed 44 academic articles written between 1996 and 2019 and analyzed concepts of place quality spanning the disciplines of urban design, urban planning, and urban economics. We identified three dimensions commonly associated with quality of place: a spatial dimension associated with aesthetic qualities of urban spaces; a socio-cultural dimension associated with experienced “sense of place”; and an economic dimension associated with the agglomeration of economic activities. Then we worked out these three dimensions in the context of HSR station areas and attributed features accordingly. We concluded that the economic dimension far outweighs the others in academic debates, with dominant theories being primarily concerned with land use, accessibility, and economic performance. Studies from the urban design field have tackled the spatial elements of place quality and showed a strong correlation with economic dimension. However, the literature remains insufficiently developed when it comes to addressing user experience and “sense of place.”